Confucian Values and Ethical Leadership in Sustainable SME Development - Budi Sutiono Pratama Nugraha; Novi Diah Wulandari; Marosimy Millaty (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines how Confucian cultural values—Ren, Yi, Li, and Zhi—shape ethical leadership and sustainability practices in small and medium-sized enterprises (SMEs), thereby contributing to the implementation of the Sustainable Development Goals (SDGs) in emerging economies. Ethical Leadership is investigated as a mediating mechanism linking cultural values to sustainability outcomes. A phenomenological qualitative approach was employed through in-depth interviews with 15 SME leaders selected using purposive sampling. Data were analyzed using thematic analysis and the Gioia methodology, progressing from first-order concepts to second-order themes and aggregate dimensions to explore the relationship between cultural values, leadership behavior, and sustainability practices. The findings show that Ren promotes social responsibility through employee welfare and community engagement, while Yi strengthens ethical decision-making based on fairness and integrity. Li institutionalizes ethical conduct through organizational norms and governance systems, whereas Zhi supports a long-term orientation toward sustainability. Ethical Leadership emerged as the key mechanism translating these values into sustainability-oriented practices aligned with the SDGs. Leaders who embody Confucian values foster trust, legitimacy, and stakeholder engagement, creating a culture that supports sustainable business practices. The study highlights a culturally embedded pathway of sustainability transformation in SMEs by integrating value-based Leadership and ethical governance. It contributes to leadership theory by conceptualizing ethical Leadership as a culturally grounded and value-driven process rather than a universal behavioral construct. In practice, the findings suggest that integrating Confucian ethics into leadership development programs can strengthen ethical governance, sustainable performance, and alignment with the SDGs in culturally diverse SME contexts.